Visualizing the intellectual structure and evolution of electronic health and telemedicine research. (October 2019) - Gu, Dongxiao; Li, Tongtong; Wang, Xiaoyu; Yang, Xuejie; Yu, Zhangrui
Highlights: Bibliometrics is used to comprehensively analyze the evolution track, knowledge base and research hotspots of e-health. The United States is the largest publishing country for electronic health articles, and the research cooperation among countries is very close. E-health records, telemedicine, and health information management have become the research focuses in e-health. Mobile healthcare, smart health and the deep integration of e-health information are research trends in e-health and telemedicine. Abstract: Background: In recent years, the development and application of emerging information technologies, such as artificial intelligence, cloud computing, Internet of Things, and wearable devices, has expanded the content of electronic health (e-health). Electronic health has become a research focus, but few studies have explored its knowledge structure from a global perspective. Methods: To detect the evolution track, knowledge base and research hotspots of e-health, we conducted a series of bibliometric analyses on the retrieved 3, 085 papers from the Web of Science core database in 1992–2017. We used several bibliometric tools, such as HistCite, CiteSpace, NetDraw, and NEViewer, to describe the evolution process, time-and-space knowledge map, and hotspots in e-health. Results: The research results are as follows. (a) The number of publications has been obviously increasing after 2005 and according to the trend line it is expected to continue increase exponentially in the future. (b) Countries/regions conducting e-health research have close cooperative relationship, among which European countries have the closest cooperation. (c) Electronic health records, mobile health and health information technology are research hotspots in electronic health. Moreover, scholars also pay attention to the hot issues such as privacy, security, and quality improvement. Conclusions: Electronic health is a large and growing field with quite a number of research articles in medical journals. This study provides a comprehensive knowledge structure of electronic health for scholars in the healthcare informatics field, which can help them quickly grasp research hotspots and choose future research projects.